2017
DOI: 10.1021/acs.macromol.6b02314
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector Thermal Field-Flow Fractionation for the Characterization of Vinyl Polymers in Binary Solvent Systems

Abstract: Thermal field-flow fractionation (ThFFF) is applied to the characterization of vinyl polymers such as poly(vinylcyclohexane) (PVCH) in terms of size, molar mass and chemical composition. It is shown by 1 H NMR that, although limited, ThFFF using single component solvents can separate polystyrene (PS) and its hydrogenated product, PVCH, according to differences in molecular microstructure. Different from single component solvents, binary solvent systems of cyclohexane and methyl ethyl ketone can provide an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In fact, such mixture effects can be also used to improve ThFFF separations. 81,82 The retention in ThFFF is a result of the interplay between DT and D. In particular D is strongly dependent on the mean layer temperature which corresponds to the retention time why δD for this cwPE appears to be significantly lower than reported for regular types of PE (δD = 18 MPa 0.5 for HDPE or LDPE δD = 17.6 MPa 0.5 )? 83 The trend to lower δD is also found for iso-alkanes in comparison to their n-derivates.…”
Section: Resultsmentioning
confidence: 92%
“…In fact, such mixture effects can be also used to improve ThFFF separations. 81,82 The retention in ThFFF is a result of the interplay between DT and D. In particular D is strongly dependent on the mean layer temperature which corresponds to the retention time why δD for this cwPE appears to be significantly lower than reported for regular types of PE (δD = 18 MPa 0.5 for HDPE or LDPE δD = 17.6 MPa 0.5 )? 83 The trend to lower δD is also found for iso-alkanes in comparison to their n-derivates.…”
Section: Resultsmentioning
confidence: 92%
“…In the case of alkane mixtures, significant solvent effects observed in other solvent mixtures are not expected. In fact, such mixture effects can be also used to improve ThFFF separations. , …”
Section: Resultsmentioning
confidence: 99%
“…In fact, such mixture effects can be also used to improve ThFFF separations. 83,84 The retention in ThFFF is a result of the interplay between D T and D. In particular, D is strongly dependent on the mean layer temperature, which corresponds to the retention time measured in ThFFF. Hence, the question arises: to which extent does the solubility influences D T ?…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…This interplay between the two mass transport processes forms the basis for the compositional (through D T ) or size‐based (through D ) separation capabilities of ThFFF . For a more in‐depth explanation of the ThFFF principles, the reader is referred to several articles addressing the subject …”
Section: Introductionmentioning
confidence: 99%
“…[19,24] For a more in-depth explanation of the ThFFF principles, the reader is referred to several articles addressing the subject. [24][25][26] Despite the remarkable separation capabilities of ThFFF only a few studies have addressed the characterization of star polymers by ThFFF. To date, it has been shown that ThFFF can be used to separate star and linear polymers based on differences in hydrodynamic size and that the chemical composition distributions as well as the number of arms of miktoarm star copolymers can be determined.…”
Section: Introductionmentioning
confidence: 99%